The 1945 Constitution In The Era Of Digital Disruption: Upholding Citizen Rights Against Algorithmic Challenges - Adrik Kemal Bahruniam; Eny Kusdarini (Jurnal Penegakan Hukum dan Keadilan, 2026)
It is become harder to protect constitutional rights in Indonesia, especially freedom of speech and privacy, because of the digital age. As algorithmic methods become more common on media platforms, these rights are more and more under risk since automated processes don't have enough democratic supervision. This study analyzes the effects of algorithmic governance on people' constitutional rights as delineated in the 1945 Constitution of Indonesia, emphasizing the susceptibilities of privacy and expression in the digital domain. The study used a literature review methodology to examine the influence of algorithmic systems, encompassing content filtering, data collection, and profiling, on public discourse and individual liberties. The results show that algorithmic systems, which often work in secret, violate people's rights by silencing different points of view, making biases even worse, and using data to invade privacy. The study stresses the need to reevaluate Indonesia's constitutional framework to ensure proper rights protection in the context of algorithmic governance. The study ends by suggesting changes to make algorithmic systems more open, accountable, and overseen, which would help protect people's rights in the fast-changing digital world.